Pelestarian Bacang Vegan Sebagai Kuliner Khas Kampung Wisata Tematik Ranca Indah, Serpong, Kota Tangerang Selatan - Joshua Imanuel; Talitha Ferina Aileen; Olivia; Kelly Virginia Putri; Budi Setiawan (Indonesian Journal Publisher, 2026)
Gastronomic tourism is a rapidly growing form of tourism because it integrates culinary experiences with the local cultural values of a destination. This study aims to analyze efforts to preserve vegan bacang as a signature dish of the Ranca Indah Thematic Tourism Village in Serpong, South Tangerang City, and to examine its role in supporting the development of community-based gastronomic tourism. The study employs a qualitative approach using a descriptive method. Data collection was conducted through observation, semi-structured interviews, and documentation. Informants were selected using purposive sampling, involving tourism village managers, Pokdarwis (Community-Based Tourism Group) officials, culinary business operators, and community members involved in gastronomic tourism activities. Data were analyzed using interactive analysis techniques, including data reduction, data presentation, and drawing conclusions. The results of the study indicate that culinary management in the Ranca Indah Thematic Tourism Village is carried out in a participatory manner by involving the community in the production, innovation, and promotion of local cuisine. Vegan bacang is a culinary innovation that preserves traditional processing techniques while using plant-based ingredients as an adaptation to changing consumer preferences, which are increasingly focused on health and sustainability. Beyond serving as a food product, vegan bacang functions as a vehicle for cultural preservation, a symbol of local culinary identity, a tool for gastronomic tourism education, and a source of income for the community. Nevertheless, its development still faces challenges, including limited human resources and suboptimal digital promotion. Therefore, collaboration among the community, government, academia, and industry stakeholders is essential to strengthen the management, marketing, and sustainability of community-based gastronomic tourism.